12 before 13 - Greenwald, Lisa (Greenwald, Lisa. Friendship list novel ;, 2018)
Inspired by the success of their first birthday bucket list, Ari and Kaylan set goals for the new school year but both face challenges that may threaten their friendship. After a life-changing summer at camp, Ari feels torn between Kaylan and her camp friends. And as she faces down everything from boys to bat mitzvahs, Ari needs to figure out how to be her best self--before her friends come together at her thirteenth birthday party. Or the big win she and Kaylan were hoping for may become an epic fail.